Juridical Analysis of Jarimah Zina on Married Perpetrators Based on Qanun Aceh Number 6 of 2014 concerning Jinayah (Study Decision Number: 4/JN.2021/MS. IDI) - Dainur; Riza Zarzani (Yayasan Multidimensi Kreatif, 2024)
this study discusses the crime of adultery based on Qanun Aceh Number 6 of 2014 concerning Jinayat Law and national criminal law. The Aceh Qanun provides a legal basis for the implementation of Islamic sharia in Aceh, including the enforcement of the law of adultery. One of the legal aspects regulated is the sanction of whipping for adulterers, both married and unmarried, without the need for a complaint from the husband or wife. This study also analyzes the case of adultery case number 4/JN/2021/MS. Idi, who decided the punishment of whipping against the defendant based on the confession of the adulterous jarimah. This study aims to examine the legal regulation of the crime of adultery in the national criminal law and qanun, as well as analyze law enforcement in these cases.